TRANSFORMASI KAPITAL KULTURAL MELALUI PLURILINGUALISME DAN GASTRODIPLOMASI PRANCIS-INDONESIA SEBAGAI REALITA POLITIK HIJAU PASCA PANDEMI - Asiati, Tri; Dian Adiarti,; Erna Wardani, (Journal of Innovation Research and Knowledge, 2023)
Plurilinguism is an individual's communicative competence which does not only involve verbal and non-verbal aspects, but also adaptive and adoptive abilities to cultural conventions. This linguistic political root guides speakers to be knowledgeable, experienced, sociable, synergistic and tolerant of culture, as well as eliminating culture shock in its acquisition. One of the subcultures of language speakers is food culture, which differ in values and functions between cultures. In plurilinguism, gastronomy occupies a special level, because it can function beyond its significance, namely as a diplomatic vehicle with the term gastrodiplomacy. Gastrodiplomacy is the art of negotiation by mixing and matching culture, cuisine, and the essence of nationalism to make foreign cultures real. From this concept, French-Indonesian gastrodiplomacy is rife. However, the tendency of organizing does not necessarily become a bridge between cultures. This is motivated by capitalism wrapped in popular culture. Meanwhile, the green economy as a transformation of cultural capital also determines the plurilinguism movement. Based on this, how the transformation of cultural capital refers to French-Indonesian gastrodiplomacy that is in line with the principles of post-pandemic green politics will be analyzed using netnographic methods, document studies, and observation. The primary research data are: the existence and evolution of gourmet food, the practice of gastrodiplomacy, and the form of gastrodiplomacy of the archipelago by French speakers. The result is a description of the relevance of the transformation of cultural capital to political pluralism through French-Indonesian gastrodiplomacy which is in line with post- pandemic green politics.